Video Recording of the On-site Investigation - RUSNAC, Constantin; LEVANDOVSKI, Nicolai (ACROSS (Galați), 2025)
Currently, the increasing effectiveness of criminal procedural investigations is determined by the level of implementation in the practical activity of methods and technical-scientific means intended for discovery, fixation, collection, and examination through which the missing data omitted by the person in the process of perception, memorization, saving, reproduction, systematization, and transmission of information are compensated. Thus, because of the application of technical-scientific means and methods, the evidentiary data become more precise and complete, determining new tactical possibilities for carrying out criminal prosecution actions. In this article, the authors examine the existing opinions in forensic literature on the necessity and forensic-technical rules governing the technical process of video recording of on-site investigation activity. Even though there are various technical ways of recording the on-the-spot investigation, judicial bodies are hesitant to use the video technique in the on-the-spot investigation. The circumstances requiring the use of video technology and the situations determined by them are characterized in terms of their doctrinal and empirical basis. The authors also deal with the subject of video recording which needs to be reflected in the on-the-spot investigation report.